Cervical excisional treatment increases the risk of intraamniotic infection in subsequent pregnancy complicated by preterm prelabor rupture of membranes - Kacerovsky, Marian; Musilova, Ivana; Baresova, Simona; Kolarova, Klara; Matulova, Jana; Wiik, Johanna; Sengpiel, Verena; Jacobsson, Bo (American journal of obstetrics and gynecology, 2023)
Excisional treatment of cervical intraepithelial neoplasia or very early stages of cervical cancer increases the risk of preterm prelabor rupture of membranes in subsequent pregnancies. The risk increases with the length of the excised cone. The subset of cases with preterm prelabor rupture of membranes and a history of cervical excisional treatment could also be at higher risk of intraamniotic infection/inflammation. However, there is a paucity of relevant information on this subject. This study aimed to assess the differences in the rates of intraamniotic infection/inflammation and early-onset neonatal sepsis between singleton preterm prelabor rupture of membranes pregnancies without and with a history of cervical excisional treatment, and to investigate the association between these complications of preterm prelabor rupture of membranes and the excised cone length. This retrospective cohort study included 770 preterm prelabor rupture of membranes pregnancies in which transabdominal amniocentesis was performed as part of standard clinical management to assess the intraamniotic environment. The maternal and perinatal medical records of all included women were reviewed to obtain information on the absence or presence of history of cervical excisional treatment and neonatal outcomes. Women whose records contained any information on history of cervical excisional treatment were contacted by phone and in writing to inform them of the study and request permission to collect relevant information from their medical records. Women were divided into 4 subgroups according to the presence of microorganisms and/or their nucleic acids (through culturing and molecular biology methods) in amniotic fluid and/or intraamniotic inflammation (through amniotic fluid interleukin-6 concentration evaluation): intraamniotic infection (presence of both), sterile intraamniotic inflammation (intraamniotic inflammation alone), microbial invasion of the amniotic cavity without inflammation (presence of microorganisms and/or their nucleic acids in amniotic fluid alone), and negative amniotic fluid for infection/inflammation (absence of both). A history of cervical excisional treatment was found in 10% (76/765) of the women. Of these, 82% (62/76) had a history of only 1 treatment, and information on cone length was available for 97% (60/62) of them. Women with a history of cervical excisional treatment had higher rates of intraamniotic infection (with, 25% [19/76] vs without, 12% [85/689]; adjusted odds ratio, 2.5; adjusted P=.004), microbial invasion of the amniotic cavity without inflammation (with, 25% [19/76] vs without, 11% [74/689]; adjusted odds ratio, 3.1; adjusted P<.0001), and early-onset neonatal sepsis (with, 8% [11/76] vs without, 3% [23/689]; adjusted odds ratio, 2.9; adjusted P=.02) compared with those without such history. Quartiles of cone length (range: 3–32 mm) were used to categorize the women into 4 quartile subgroups (first: 3–8 mm; second: 9–12 mm; third: 13–17 mm; and fourth: 18–32 mm). Cone length of ≥18 mm was associated with higher rates of intraamniotic infection (with, 29% [5/15] vs without, 12% [85/689]; adjusted odds ratio, 3.0; adjusted P=.05), microbial invasion of the amniotic cavity without inflammation (with, 40% [6/15] vs without, 11% [74/689]; adjusted odds ratio, 6.1; adjusted P=.003), and early-onset neonatal sepsis (with, 20% [3/15] vs without, 3% [23/689]; adjusted odds ratio, 5.7; adjusted P=.02). History of cervical excisional treatment increases risks of intraamniotic infection, microbial invasion of the amniotic cavity without inflammation, and development of early-onset neonatal sepsis in a subsequent pregnancy complicated by preterm prelabor rupture of membranes.